Low prevalence of transfusion-transmissible infections among voluntary blood donors in South India - Manoharan Mythreyee; Chinnappan Jayachandran; Murugesan Amudhan; Moorthy Sivashankar; Nagasundaram Mythily; Ramalingam Sekar (Journal of Infection in Developing Countries)
This item has no abstract. Follow the link below to access the full text.